The mental health and wellbeing of adolescents on remand in Australia - Sawyer, M.; Guidolin, M.; Schulz, K.; McGinnes, B.; Zubrick, Stephen; Baghurst, P. (Informa Healthcare, 2010)
AbstractOBJECTIVE: To compare the nature and prevalence of mental health problems, prevalence of suicidal ideation and behaviour, and health-related quality of life of 13-17-year-olds on remand with that of 13-17-year-olds in the general community.METHOD: Self reported questionnaires completed by 13-17-year-olds who were remanded in South Australia in 2008/9 (N = 159), 13-17-year-olds who participated in the Child and Adolescent Component of the National Survey of Mental Health and Well-being in Australia (N = 1283), and 13-17-year-olds who participated in the Western Australian Aboriginal Child Health Survey (N = 1100). Mental health problems were identified using the Youth Self-Report and the Strength and Difficulties Questionnaire. Health-related quality of life was assessed using the Child Health Questionnaire.RESULTS: A total of 50.0% (95% CI, 42.3-58.3) of adolescents on remand versus 18.9% of adolescents in the community scored above the recommended cut-off score on the Youth Self-Report. Among Indigenous adolescents, 55.8% (95% CI, 41.3-69.5) on remand versus 32.1% in the community scored above the recommended cut-off score on the Strength and Difficulties Questionnaire. Among those on remand, 19.1% (95% CI, 13.2-26.2) reported making a suicide attempt during the previous 12 months compared to 4.3% in the community. Health-related quality of life was significantly worse among adolescents on remand than adolescents in the community. These differences remained after adjusting for differences in the demographic characteristics of the two groups of adolescents.CONCLUSIONS: Compared with adolescents in the community, both Indigenous and non-Indigenous adolescents on remand experience a wide range of problems, including poorer mental and physical health, a higher prevalence of suicidal ideation and behaviour, greater family adversity, and poorer school attendance. This broad range of problems needs to be effectively addressed to enable adolescents on remand to become active and productive members of their communities.